Dependence of heart rate variability on indicators of type 1 diabetes mellitus control. - N. O. Pertseva; O. V. Gurzhiy; K. I. Moshenets (Medičnì Perspektivi)
The aim of our study was to evaluate the influence of the main indicators of type 1 diabetes mellitus (T1DM) control on heart rate variability (HRV). We examined 62 patients at the age of 18-45 years with an average T1DM duration of 11.0 (5.0; 18.0) years. HRV in the time and frequency range was evaluated by analyzing a 24-hour Holter electrocardiogram (ECG). The following laboratory parameters were used as markers of course and compensation of T1DM: C-peptide, HbA1c, blood creatinine, albuminuria (AU), estimated glomerular filtration rate (eGFR) by CKD-EPI formula. In addition, the maximum and minimum blood glucose levels and the blood glucose range (maximum minus minimum blood glucose values) were conducted by continuous glucose monitoring system iPro2 (Medtronic MiniMed, USA). The daily monitoring of electrocardiogram (ECG) was made in parallel with long term monitoring of blood glucose. Echocardiography in all patients was performed to exclude organic heart disease and the possibility of its influence on HRV. Poor control of T1DM negatively influences HRV through decrease in both frequency and time characteristics. The blood glucose range can be an additional negative factor for cardiovascular system in T1DM patients, regardless of HbA1c, whereas it positively correlates with HRV- relative hypersympathicotonia markers: LF/HF 24-h, ρ=0.43 (p<0.05), LF/HF day ρ=0.37 (p<0.05), ρ=0.38 LF/HF night. Diabetic nephropathy is another factor of cardiovascular disease progression in T1DM, since its criteria have reliably negative (for eGFR) and positive (for AU) correlations of mean force with all HRV characteristics. Selected markers of T1DM control cause 45, 73% of variance in HRV, mainly affecting TP 24-h, TP daytime, VLF 24-h, VLF daytime. Reduction of these frequency HRV characteristics may indicate autonomic neuropathy in patients with poor control of T1DM.